Níveis de maturidade em programas de conservação auditiva em indústrias e a percepção do risco por trabalhadores - Wictor, Ieda Claudia (2016)
The high level of occupational noise is a problem present in all regions of the world. Noise is an environmental agent that daily affects a large number of workers in industries and generate countless negative consequences. Research on occupational noise and the health effects of the worker is published, however, the analysis of individual perception of the worker on his behavior is still a subject little addressed. This research aimed to evaluate the influence of the level of maturity of the Hearing Conservation Programs on the perception of risk by the workers. The present study evaluated five metallurgical companies with a sample of 243 workers exposed to sound pressure levels above the action level in national legislation 85 dB (A). Based on the bibliographic review, two questionnaires were used to evaluate qualitative variables. The first questionnaire was developed and applied to companies to evaluate maturity levels in auditory conservation programs. Subsequently a questionnaire was applied to the worker considering the individual perception of risk, perception of the effects of noise, safety culture and risk behavior. The data were analyzed statistically, where tools of reliability analysis, analysis of variance - ANOVA, Tukey test and descriptive statistics were used to relate the data. It was concluded that the different levels of maturity do not present significant differences in the perception of the worker, however, it was possible to verify a greater perception of risk in the different levels of exposure to noise.